A Pragmatic Phenomenon of Conversation (Texas Journal of Philology, Culture and History, 2023)
Pragmatics and sociolinguistics view the speech acts as the smallest unit of analysis in any speech event. The latter is defined as a “socially accepted” and “patterned sequence” in which the participants of specific speech community are involved. speech community is used to a group of participants who intuitively know how to behave in a speech event. Examples of the speech events are conversations, jokes, sermons, interview, prayers or political speeches (penalosa,198:71)